2011
DOI: 10.1093/aob/mcr205
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms controlling legume autoregulation of nodulation

Abstract: Nodulation is regulated primarily via a systemic mechanism known as the autoregulation of nodulation (AON), which is controlled by a CLAVATA1-like receptor kinase. Multiple components sharing homology with the CLAVATA signalling pathway that maintains control of the shoot apical meristem in arabidopsis have now been identified in AON. This includes the recent identification of several CLE peptides capable of activating nodule inhibition responses, a low molecular weight shoot signal and a role for CLAVATA2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
234
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(248 citation statements)
references
References 80 publications
8
234
0
6
Order By: Relevance
“…First, an internal regulation leads to an "auto-regulation of nodule number" (AON) by the host plant, through a systemic feedback repression of nodulation by pre-existing nodules (Reid et al 2011;Mortier et al 2012 for reviews). Deregulated mutants with a hypernodulating phenotype were isolated in several legume species (Novak 2010;Reid et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, an internal regulation leads to an "auto-regulation of nodule number" (AON) by the host plant, through a systemic feedback repression of nodulation by pre-existing nodules (Reid et al 2011;Mortier et al 2012 for reviews). Deregulated mutants with a hypernodulating phenotype were isolated in several legume species (Novak 2010;Reid et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…First, an internal regulation leads to an "auto-regulation of nodule number" (AON) by the host plant, through a systemic feedback repression of nodulation by pre-existing nodules (Reid et al 2011;Mortier et al 2012 for reviews). Deregulated mutants with a hypernodulating phenotype were isolated in several legume species (Novak 2010;Reid et al 2011). In the case of pea (Pisum sativum L.), hypernodulating mutants have been selected after mutagenesis and three genes have been shown to be involved in the regulation of nodulation, namely NOD3 (Postma et al 1988), SYM29, and SYM28 (Sagan and Duc 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the genetic regulation of the developmental plasticity responses to N. Some of the first identified genes regulating N phenotypes are a class of genes regulating nodule number by a systemic mechanism called autoregulation (Reid et al, 2011b). Mutation of these autoregulation genes causes supernodulation, mostly even in the presence of high N concentrations, and were thus first termed nitrate tolerant symbiotic (nts) mutants in soybean (Glycine max; Carroll et al, 1985aCarroll et al, , 1985b.…”
mentioning
confidence: 99%
“…This phase is very important for creating source of channelizing the energy at later stage. In the last and most important phase winter legumes faces heat injury, resulting in early onset of reproductive phase, causing imbalance in resources and inputs, biotic stress and forced maturity (Joshi, 1998;Dixit et al 2009;Reid et al, 2011 andSingh et al, 2012). To improve the winter legumes production under late sown conditions of Indian IGP, critical examination of situation revealed that, interventions to boost vegetative growth during early and mid-phase of life, to create base / source is the basic necessity that can be achieved by accelerated vegetative growth, and finally unilateral translocation of photosynthate to sink during reproductive stage (Guilfoyle andHagen, 2001and Pandey andGautam, 2009) are therefore essential.…”
Section: Why Water Management Is So Important In Grain Legume Productmentioning
confidence: 99%